The Effect of Green Accounting, Corporate Social Responsibility on Profitability - Marsuking; Abi Suryono; Setiorini, Kusumaningdiah Retno (CV. Civiliza Publishing, 2025)
This study aims to examine the influence of green accounting, corporate social responsibility (CSR), and profitability, with the research object being manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020 to 2024 period. A total of 28 manufacturing companies were selected as samples, with a five-year observation period. The data used in this study are secondary data obtained from company financial reports accessed through the official IDX website at www.idx.co.id. The sampling technique used was purposive sampling, which involves selecting samples based on specific criteria relevant to the research objectives. Data analysis was carried out using descriptive analysis and multiple linear regression analysis. The results of the analysis show that the green accounting variable has a significance value of 0.381, which exceeds the 0.05 threshold, and a t-value of -0.878, which is lower than the t-table value (1.977). This indicates that green accounting does not have a significant effect on company profitability. Additionally, the negative t-value suggests that the relationship between these two variables is not in the same direction. Meanwhile, the CSR variable shows a significance value of 0.033, which is less than 0.05, and a t-value of 2.158, which is greater than the t-table value. These findings indicate that CSR has a significant and positive effect on profitability. The Adjusted R² value of 0.047 or 4.7% indicates that green accounting, CSR collectively explain 4.7% of the variation in profitability as measured by Return on Assets (ROA), while the remaining 95.3% is influenced by other factors not included in this research model.